2021
DOI: 10.1186/s12890-021-01716-y
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance tomography in pediatric patients with COVID-19, the first reports

Abstract: Introduction Electrical impedance tomography (EIT) is a noninvasive, radiation-free, bedside tool to monitor ventilation distribution in real time. Objective To evaluate, in pediatric COVID-19 patients, the ventilation distribution using EIT and compare it to thoracic computed tomography (TCT) or chest radiograph results obtained in these patients. Methods This was a prospective, observational clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For example, Draeger Medical Devices has developed the first commercial EIT equipment for pulmonary function monitoring and conducted several clinical studies ( Bickenbach et al, 2017 ; Eronia et al, 2017 ; Longhini et al, 2019 ; Zhao et al, 2019 ). Particularly during the COVID-19 pandemic, EIT has provided a potential reference for the decision-making of patients' treatment ( Hsu et al, 2021 ; Nascimento et al, 2021 ; Bayford et al, 2022 ), thereby demonstrating the significant clinical application value of pulmonary EIT in the management of patients suffering from severe respiratory failure ( Zhao et al, 2020 ; Bronco et al, 2021 ). In the case of brain injury monitoring, Fu et al demonstrated the important role of EIT in the treatment of mannitol dehydration ( Fu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Draeger Medical Devices has developed the first commercial EIT equipment for pulmonary function monitoring and conducted several clinical studies ( Bickenbach et al, 2017 ; Eronia et al, 2017 ; Longhini et al, 2019 ; Zhao et al, 2019 ). Particularly during the COVID-19 pandemic, EIT has provided a potential reference for the decision-making of patients' treatment ( Hsu et al, 2021 ; Nascimento et al, 2021 ; Bayford et al, 2022 ), thereby demonstrating the significant clinical application value of pulmonary EIT in the management of patients suffering from severe respiratory failure ( Zhao et al, 2020 ; Bronco et al, 2021 ). In the case of brain injury monitoring, Fu et al demonstrated the important role of EIT in the treatment of mannitol dehydration ( Fu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been applied to pediatric patients with COVID-19 (Nascimento et al 2021). EIT has been successfully used to observe bronchodilator effects in both children and adults (Frerichs et al 2016, Ngo et al 2018.…”
Section: Introductionmentioning
confidence: 99%